Reign of Raja Syed Alwi Ibn Syed Safi Jamalullail in Perlis (1905-1943) : modernisation and socioeconomic development - Arba'iyah Mohd Noor,; Mohd Firdaus Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Perlis was seldom in the limelight since it was part of Kedah. From the 14th to 17th century, seven generations of the Kedah Sultanate had thrived in Kota Si Puteh (in Kubang Pasu District) since it was located approximately three miles from the border of Perlis or 18 to 19 miles if the distance is measured from Perlis river to Kuala Perlis beach. This article will discuss the modernisation and socioeconomic development during the reign of Raja Syed Alwi Jamalullail in Perlis between 1905 to 1943. The objectives of this research is to discuss how Raja Syed Alwi managed to restore the economic problems of Perlis once he ascended the throne. The objective of this article is to discuss the socio-economic development during his reign. The methodology of the study is a qualitative method based on historical discipline. This study found that during the reign of Raja Syed Alwi Jamalullail, there was a process of modernisation and some development in socio-economic aspects. Although in the early stages of his reign he had faced financial issues, he managed to solve those problems, formed the Perlis State Council Meeting and planned some socio-economic developments that led to modernisation for the state of Perlis.